THE EFFECT OF COMPENSATION AND CAREER OPPORTUNITIES ON JOB SATISFACTION OF EMPLOYEES OF THE LHOKSUKON SHARIA COURT, NORTH ACEH REGENCY - Sutan Febriansyah; Yusnidar; Almunadiya; Rahmiatul Aula; Raudhatinur; Raudhatul Jannah (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
In the modern era, human resource development is very important and crucial because it produces employees who are innovative, creative, have initiative, able to solve problems, have broad expertise, and have extraordinary work abilities. The purpose of this study is to determine whether Motivation and Job Satisfaction Influence the Performance of Employees of the 92nd Representative Office of Bank Indonesia Lhokseumawe. Sample determination uses the slovin formula with a sample size of 1,000 people. The results of the study say that Motivation and Job Satisfaction have a positive and significant effect on the Performance of Employees of the Lhokseumawe Representative Office of Bank Indonesia. In the Anova test or F-test, motivation and job satisfaction together have a significant effect on the Performance of Employees of the Lhokseumawe Representative Office of Bank Indonesia. Determination of the results of the data study shows that the R2 value is 0.578 or 57.8%, this illustrates that the influence of Motivation and Job Satisfaction on the Performance of Employees of the Lhokseumawe Representative Office of Bank Indonesia is 57.8% and the remaining 42.3% is influenced by other unknown variables and is not included in this regression analysis.